Teacher education in Australia - Nordin, Mohd Norazmi; Ibrahim, Nor Idayu; Borhanordin, Amirah Hazimah; Abd Halim, Wan Ismail; Mustafa, Mohamad Zaid (Türkiye Fizyoterapistler Derneği, 2021)
In this study, the researcher describes about the landscape of teacher education in Australia as a developed country and the issues that arise in the implementation of teacher education in that country. In addition, the researcher also briefly inserts the relevance of history, geography and culture in the current of education in general and the influence of teacher education in particular. Through several previous studies, the researcher briefly explains that education in Australia is also influenced by various factors in determining its landscape as well as its practices. The formation of the education system in a country also involves historical influences involving colonial intervention, diverse cultural values, ethnicity and the position of a country. The discussion of this review article is expected to provide a brief overview to the next researcher related to teacher education in Australia.